Therapeutic Approaches to Nonalcoholic Fatty Liver Disease: Exercise Intervention and Related Mechanisms - Takahashi, Hirokazu; Kotani, Kazuhiko; Tanaka, Kenichi; Egucih, Yuichiro; Anzai, Keizo (Frontiers in Endocrinology, 2018)
Exercise training improves nonalcoholic fatty liver disease (NAFLD) as well as obesity and metabolic diseases. Although it is difficult to eliminate the effects of body weight reduction and increased energy expenditure, which are among the pleiotropic effects of exercise training, a number of clinical and experimental studies involving either aerobic exercise training or resistance training programs show improvements in NAFLD that are independent of the improvements in obesity and insulin resistance. In vivo studies have identified effects of exercise training on the liver, which may help to explain the “direct” or “independent” effect of exercise training on NAFLD. Exercise training increases peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC1α) expression, improves mitochondrial function and leads to reduced hepatic steatosis, inflammation, fibrosis, and tumor genesis. Crosstalk of liver to adipose tissue, skeletal muscle and the microbiome is also a possible mechanism for the effect of exercise training on NAFLD. Although numerous clinical and experimental studies have reported benefits of exercise training on NAFLD, the optimal duration and intensity of exercise for the prevention or treatment of NAFLD have not been established. Maintaining adherence of NAFLD patients to exercise training is another issue to be resolved. The use of comprehensive analytical approaches to identify biomarkers such as hepatokines that specifically reflect the effect of exercise training on liver may help to monitor the exercise effect on NAFLD, and thereby improve adherence of NAFLD patients to exercise training. Exercise training is a robust approach for improving NAFLD pathogenesis, though further clinical and experimental study is required.